Effects of speech phonological features during passive perception on cortical auditory evoked potential in sensorineural hearing loss - Hua, Nong Ting; Abdul Rauf A Bakar,; Jayasree Santhosh,; Mohammed G. Al-Zidi,; Ibrahim Amer Ibrahim,; Ng, Siew Cheok (Penerbit Universiti Kebangsaan Malaysia, 2017)
The deficiency in the human auditory system of individuals suffering from sensorineural hearing loss (SNHL) is known to be associated with the difficulty in detecting of various speech phonological features that are frequently related to speech perception. This study investigated the effects of speech articulation features on the amplitude and latency of cortical auditory evoked potential (CAEP) components. The speech articulation features included the placing contrast and voicing contrast. 12 Malay subjects with normal hearing and 12 Malay subjects with SNHL were recruited for the study. The CAEPs response recorded at higher amplitude with longer latency when stimulated by voicing contrast cues compared to that of the placing contrast. Subjects with SNHL elicited greater amplitude with prolonged latencies in the majority of the CAEP components in both speech stimuli. The existence of different frequency spectral and time-varying acoustic cues of the speech stimuli was reflected by the CAEPs response strength and timing. We anticipate that the CAEPs responses could equip audiologist and clinicians with useful knowledge, concerning the potential deprivation experience by hearing impaired individuals, in auditory passive perception. This would help to determine what type of speech stimuli that might be useful in measuring speech perception abilities, especially in Malay Malaysian ethic group, for choosing a better rehabilitation program, since no such study conducted for evaluating speech perception among Malaysian clinical population.